2006
DOI: 10.1300/j160v06n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Substance-Abusing Women and Their Children: A Cost-Effective Treatment Option to Incarceration

Abstract: Low-level drug offenses are presently the top reason women are sent to jail. Because more than 70% of these incarcerated women are the primary caretakers of children, incarceration has resulted in a sharp rise in foster care demand. Research suggests that incarcerated women who remain with their children are more likely to enter and complete treatment. This paper reviews the effects of incarceration and the available treatment options for substance-abusing women with children. A self-supported, self-run, alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…[38] However, there are reportedly few 818 Grade 1 schoolchildren Combined FAS and PFAS prevalence of 68.0 -89.2/1 000 [13] 857 Grade 1 schoolchildren FAS prevalence of 65.2 -74.2/1 000 [6] Grade 1 schoolchildren FAS rate of 40.5 -46.4/1 000 [14] Gauteng Combined FAS and PFAS prevalence of 119/1 000 [5] Upington Grade 1 schoolchildren at 15 schools Combined FAS and PFAS prevalence of 74.4/1 000 [5] public sector alcohol and other drug abuse treatment facilities available in SA. [39] Punishing women for failing to seek treatment that may actu ally not be available would therefore be unjust.…”
Section: Not Evidence Basedmentioning
confidence: 99%
See 2 more Smart Citations
“…[38] However, there are reportedly few 818 Grade 1 schoolchildren Combined FAS and PFAS prevalence of 68.0 -89.2/1 000 [13] 857 Grade 1 schoolchildren FAS prevalence of 65.2 -74.2/1 000 [6] Grade 1 schoolchildren FAS rate of 40.5 -46.4/1 000 [14] Gauteng Combined FAS and PFAS prevalence of 119/1 000 [5] Upington Grade 1 schoolchildren at 15 schools Combined FAS and PFAS prevalence of 74.4/1 000 [5] public sector alcohol and other drug abuse treatment facilities available in SA. [39] Punishing women for failing to seek treatment that may actu ally not be available would therefore be unjust.…”
Section: Not Evidence Basedmentioning
confidence: 99%
“…[39] Punishing women for failing to seek treatment that may actu ally not be available would therefore be unjust. Moreover, prisons are often inadequately equipped to provide for the specialised needs of pregnant women and children, [38] and there are concerns about the mental and emotional effects of children growing up in prisons.…”
Section: Not Evidence Basedmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents who experience addiction, especially those who have been convicted of felony offenses, frequently have difficulty securing affordable housing and gainful employment, which perpetuates a vicious cycle of poverty and relapse (Jason, Olson, Foli, 2008). Unstable housing and employment may also affect parents’ ability to maintain child custody while struggling with addiction or being able to sufficiently provide for a family (d’Arlach, Curtis, Ferrari, Olson, & Jason, 2006). …”
mentioning
confidence: 99%
“…Another novel feature of some OHs is the capacity to allow children to live in these settings with their parents (d’Arlach, Curtis, et al, 2006). Ortiz, Alvarez, Jason, Ferrari, and Groh (2009) compared the characteristics of individuals living in OHs with and without children and concluded that women in OHs who care for children may require additional resources and assistance compared to men.…”
mentioning
confidence: 99%